SYNTHESIS, CHARACTERIZATION, AND APPLICATION OF Fe3O4 NANOPARTICLES AS A SIGNAL AMPLIFIER ELEMENT IN SURFACE PLASMON RESONANCE BIOSENSING - I Putu Tedy Indrayana (JOURNAL ONLINE OF PHYSICS, 2020)
The Fe3O4 nanoparticle has potential applications to be active materials for biosensor. This research was aimed at synthesizing and applying Fe3O4 nanoparticles for signal amplification of Surface Plasmon Resonance (SPR)-based biosensor. The synthesis was carried out by using the coprecipitation method at a temperature of 80oC for 60 minutes. NaOH of 5 molars was used as a precipitating agent. The Fe3O4 nanoparticles were characterized for their microstructure by using X-Ray Diffraction (XRD) and Transmission Electron Microscopy (TEM) techniques. The crystallinity of nanoparticles is 87% and the crystallite size is 15.70 nm. The shape of Fe3O4 is nearly spherical. The optical properties were characterized by using Fourier Transform Infrared Spectroscopy (FTIR) and Specular Reflection UV-Vis Spectroscopy (SR UV-Vis). There were vibrations of Fe3+-O and Fe2+-O bonds at characteristic frequencies of 586.86 cm-1 and 422.64 cm-1. The direct and indirect optical gap energies were 3.43 eV and 3.10 eV. The magnetic properties measured by Vibrating Sample Magnetometer (VSM) confirmed that Fe3O4 was ferrimagnetic. The Fe3O4 was successful to be applied as a signal amplifier for SPR-based biosensors due to their optical and magnetic properties. The SPR angle shifted to a higher value and the change was 3.57o.